A simple colorimetric analytical assay using gold nanoparticles for specific detection of tetracycline in environmental water samples. Issue 27 (28th June 2018) - Qi, Mengyu; Tu, Chunyan; Dai, Yuanyuan; Wang, Weiping; Wang, Aijun; Chen, Jianrong
Abstract : In this work, an aptamer-based colorimetric method for the detection of tetracycline (TC) was established by employing gold nanoparticles (AuNPs) as the colorimetric probe. Abstract : In this work, an aptamer-based colorimetric method for the detection of tetracycline (TC) was established by employing gold nanoparticles (AuNPs) as the colorimetric probe. In the absence of TC, the aptamers are readily adsorbed on the surface of AuNPs, which prevents aggregation of AuNPs and stabilizes the red colloidal solution against high concentrations of NaCl. In the presence of TC, the aptamers are subsequently released from the surface of the AuNPs due to binding with TC molecules. A gradual color change from red to blue was observed due to the salt-induced aggregation of AuNPs. Furthermore, a linear relationship between the absorbance intensity and the concentration of TC was observed in the range of 0.10 to 5.00 μM. The limit of detection was 0.071 μM. The developed assay was employed for the determination of TC in environmental water samples. The recoveries ranged from 106.7% to 115.6% with relative standard deviations being less than 3.0%. The results demonstrate that the method serves as a promising tool for the rapid, simple and cost-effective detection of TC.